Data assimilation in dynamical cognitive science. Issue 2 (February 2022) - Engbert, Ralf; Rabe, Maximilian M.; Schwetlick, Lisa; Seelig, Stefan A.; Reich, Sebastian; Vasishth, Shravan
Abstract : Dynamical models make specific assumptions about cognitive processes that generate human behavior. In data assimilation, these models are tested against time-ordered data. Recent progress on Bayesian data assimilation demonstrates that this approach combines the strengths of statistical modeling of individual differences with the those of dynamical cognitive models.